2010
DOI: 10.1371/journal.ppat.1000896
|View full text |Cite
|
Sign up to set email alerts
|

Infidelity of SARS-CoV Nsp14-Exonuclease Mutant Virus Replication Is Revealed by Complete Genome Sequencing

Abstract: Most RNA viruses lack the mechanisms to recognize and correct mutations that arise during genome replication, resulting in quasispecies diversity that is required for pathogenesis and adaptation. However, it is not known how viruses encoding large viral RNA genomes such as the Coronaviridae (26 to 32 kb) balance the requirements for genome stability and quasispecies diversity. Further, the limits of replication infidelity during replication of large RNA genomes and how decreased fidelity impacts virus fitness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
468
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(492 citation statements)
references
References 61 publications
20
468
0
4
Order By: Relevance
“…For SARS-CoV and Murine hepatitis virus (MHV)-A59, by contrast, viable ExoN active-site mutants could be obtained, even though they also displayed defects in RNA synthesis and virus reproduction. 67,68 Consistent with a role of ExoN in proofreading, replication fidelity of MHV-A59 and SARS-CoV encoding substitutions of residues critical for ExoN activity was found to be reduced about 15 and 21-fold compared to wildtype MHV and SARS-CoV, respectively. More detailed analysis of SARS-CoV revealed that the defect led to higher diversity ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Possible Role Of Exon In Increasingmentioning
confidence: 59%
See 2 more Smart Citations
“…For SARS-CoV and Murine hepatitis virus (MHV)-A59, by contrast, viable ExoN active-site mutants could be obtained, even though they also displayed defects in RNA synthesis and virus reproduction. 67,68 Consistent with a role of ExoN in proofreading, replication fidelity of MHV-A59 and SARS-CoV encoding substitutions of residues critical for ExoN activity was found to be reduced about 15 and 21-fold compared to wildtype MHV and SARS-CoV, respectively. More detailed analysis of SARS-CoV revealed that the defect led to higher diversity ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Possible Role Of Exon In Increasingmentioning
confidence: 59%
“…No statistically significant increase in diversity between passages could be observed, suggesting selection of advantageous (and counterselection of deleterious) mutations during virus propagation in cell culture. Eckerle et al 67 calculated a higher-than-average replication fidelity of SARS-CoV and MHV (9.0 x 10 -7 and 2.5 x 10 -6 substitutions, respectively, per nucleotide per replication cycle) when compared to other RNA viruses, while the average replication fidelity of SARS-CoV and MHV mutants encoding substitutions of ExoN active-site residues was similar to that calculated for other RNA viruses. Although these calculations probably underestimate mutation frequencies as the studies were performed with infectious viruses (counterselecting mutants with non-viable genotypes), they provide convincing evidence for ExoN playing a major role in securing a relatively high replication fidelity, similar to that reported for small DNA viruses.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, next-generation sequencing (NGS) techniques can generate massive amounts of genetic data, which can be used to detect variants at much lower frequencies (Wang et al 2007;Eriksson et al 2008;Solmone et al 2009;Cordey et al 2010;Eckerle et al 2010;Murcia et al 2010;Zagordi et al 2010;Willerth et al 2010;Bunnik et al 2011;Guo et al 2011;Wrigth et al 2011). In this study, we have generated tens of millions of short reads with Illumina sequencing to obtain an unprecedented ultradeep coverage of amiR targets in the TuMV genome, thus characterizing in great detail the genetic composition of TuMV lineages evolving in WT and 10-4 plants at different time points during the experimental evolution process and right after the first successful infection of 12-4-resistant plants.…”
Section: Introductionmentioning
confidence: 99%
“…Although in general the limited length of Illumina reads makes it difficult to assess linkage among mutations, in our particular case this was not an issue because the 21-nt sequences corresponding to the amiR159-HC-Pro target were completely covered by the 76-nt-long reads. The validity of the Illumina technology for assessing virus diversity has been proved with studies of the severe acute respiratory syndrome coronavirus (Eckerle et al 2010), human rhinovirus (Cordey et al 2010), HIV-1 (Willerth et al 2010), and foot-and-mouth disease virus (Wrigth et al 2011). …”
Section: Introductionmentioning
confidence: 99%